Immunologic characterization of patients with chronic mucocutaneous candidiasis disease. Issue 1 (4th December 2018) - Khalsa, Kiranjit K.; Yang, Qi; Shen, Xiaofei; Pasha, M. Asghar; Celestin, Jocelyn
Key Clinical Message: Even if initial immunologic screen is normal, a high index of suspicion for immunodeficiency should guide the evaluation and management of patients with recurrent episodes of mucocutaneous candidiasis. Although rare, a diagnosis of chronic mucocutaneous disease should always be considered in order to improve their outcome. Abstract : Even if initial immunologic screen is normal, a high index of suspicion for immunodeficiency should guide the evaluation and management of patients with recurrent episodes of mucocutaneous candidiasis. Although rare, a diagnosis of chronic mucocutaneous disease should always be considered in order to improve their outcome.